PROMOTING PHYSICAL ACTIVITY AMONG AT-RISK OLDER ADULTS: THE IMPACT FROM PHYSICAL AND MENTAL HEALTH. (11th November 2018) - Ory, M; Towne, S; Du, Y; Lee, S; Smith, M
Abstract: The Centers for Disease Control and Prevention (CDC) recommend at least 150 minutes moderate or 75 minutes vigorous physical activity (MVPA) per week for all adults. However, research has shown that older adults were less likely to meet the guideline and prone to falling risks. Using a state-certified community intervention program for older adults, we examined pre-post change in self-reported MVPA. The 20-session program met approximately twice a week and organized in-class group exercise. To understand the impact from physical and mental health, we analyzed results of individuals within different categories of scale-measured Body Mass Index, self-reported sleep, and depression measured by the Patient-Health-Questionnaire-4 scale. We studied 115 participants who received sufficient amount of intervention and reported both pre- and post- MVPA. The mean age was 74.1 (SD=7.7, range 61~91), and 80% were female. 88 individuals (76.5%) did not meet the CDC-guideline (i.e. at-risk). All at-risk participants improved in weekly MVPA minutes (all p<.05). The average improvement of the normal-weighted, over-weighted, and obese were 117.3 minutes, 146.4 minutes, and 73.1 minutes, respectively. Individuals reported sleep problem improved by 99.8 minutes, while others 136.0 minutes. Those with depression problems improved 114.8 minutes, and the no-depression group 104.1 minutes. The program has improved MVPA of participants, especially those at-risk. Besides, it has encouraged those commonly disadvantaged group (overweight or obese, with sleep or depression problems) to increase their physical activity level. Further investigations are necessary for the validation and generalization of this program to influence a broader population.